2005
DOI: 10.1523/jneurosci.3760-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Segregation of Different Modes of Movement Control in the Whisker Representation of Rat Primary Motor Cortex

Abstract: What is mapped on the surface of the primary motor cortex (M1)? The classic somatotopic map holds true on the level of limb representations. However, on the small scale (at within-limb representations), neither somatotopy nor movement dynamics/kinematics seem to be organizational principles. We investigated the hypothesis that integrated into the body representation of M1 there may be separate representation of different modes of motor control, using different subcortical computations but sharing the same moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
132
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(151 citation statements)
references
References 38 publications
18
132
1
Order By: Relevance
“…3, 4). A myotopic map of vM1 would clarify how the control of whisking is segregated in cortex, e.g., how do "rhythmic whisking" versus "retraction-facial" areas correspond to different patterns of intrinsic and extrinsic muscle activation (Haiss and Schwarz, 2005)? follicle alone, denoted by the subscripts h and f, respectively (Fig.…”
Section: Motor Control Of Exploratory Whiskingmentioning
confidence: 99%
“…3, 4). A myotopic map of vM1 would clarify how the control of whisking is segregated in cortex, e.g., how do "rhythmic whisking" versus "retraction-facial" areas correspond to different patterns of intrinsic and extrinsic muscle activation (Haiss and Schwarz, 2005)? follicle alone, denoted by the subscripts h and f, respectively (Fig.…”
Section: Motor Control Of Exploratory Whiskingmentioning
confidence: 99%
“…Such an hypothesis could reflect the analogy observed by Haiss and Schwarz (2005) between the representation of discrete and rhythmic movements in whisker movements in rats (see Section 6). In this model, mutual influences of movements are supposed to occur at the muscle level rather than at the spinal level, as discussed above for the Two/Two hypothesis.…”
Section: One/two Hypothesismentioning
confidence: 69%
“…Note that co-occurrence of discrete and rhythmic movements is supported by a study on whisker movements in rats by Haiss and Schwarz (2005), where it has been found that rhythmic and non rhythmic movements can be evoked through two different areas of the primary motor cortex. It has been shown in addition that simultaneous activation of both areas resulted in a shift of the offset of the whisker oscillations, that is in a combination of both movements.…”
Section: The Combination Of Discrete and Rhythmic Movementsmentioning
confidence: 74%
See 2 more Smart Citations